PENGARUH INOVASI PRODUK DAN SOSIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN KAIN TENUN DI UKM DINA - Megawati Megawati; Sri Ernawati; Muhajirin Muhajirin (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
To increase competitive advantage and maintain market share in this modern era, companies carry out many sales strategies to achieve sales performance by innovating products and using social media marketing. This type of research is associative with a quantitative approach. The sampling technique used in this research was purposive sampling with criteria such as age 20 years and over because they were considered capable of answering the questions in the questionnaire, so the number of samples in this research was 50 respondents. Data was processed using SPSS 26.0. From the results of the multiple linear regression test, there is a relationship between product innovation and social media marketing on purchasing decisions. The results of this research indicate that the product innovation variable (X1) has no effect on purchasing decisions. The research results show that the social media marketing variable (X2) has a significant effect on purchasing decisions. Product innovation and social media marketing variables have a significant influence on purchasing decisions.